Proceedings of the 2nd International Congress on Sports Sciences Research and Technology Support 2014
DOI: 10.5220/0005070001210128
|View full text |Cite
|
Sign up to set email alerts
|

Skill Scoring System for Ski’s Parallel Turns

Abstract: Dynamic posture of sports activity is one of the most important aspects to evaluate the player's skill. Such sports that need evaluation from the objective observation like figure skating and skiing have difficulty in evaluation of skill. The conventional training method for such sports was the feedback of subjective comments from the experts regarding the performance. To overcome this problem, this paper focuses on developing a new training system to give a clear guide for body balance control to the athlete.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…To our knowledge, this is the first study to date to determine turn phases by means of an IMU using kinematic criteria. A previous study already used lateral acceleration of the trunk to delimit linked turns in alpine skiing [33]. In this study, we wanted to follow this idea because of its high accuracy and precision [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first study to date to determine turn phases by means of an IMU using kinematic criteria. A previous study already used lateral acceleration of the trunk to delimit linked turns in alpine skiing [33]. In this study, we wanted to follow this idea because of its high accuracy and precision [35].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if it moves away from the horizontal axis, the acceleration is increasing. Unlike a previous study [33], we identified two main phases within the ski turn using an IMU device. INI phase was limited to the zone in which the acceleration on the Y-axis fluctuated around the zero-value corresponding to the motion between turns and all movements leading to the turn initiation.…”
Section: Criterion For Dividing Turns Into Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In alpine skiing, IMUs can offer a number of advantages that go beyond the limitations of traditional or laboratory methods [43][44][45][46][47][48][49]: compact and lightweight, easily portable and positionable, capable of wireless operation, and with the ability to capture a substantial amount of data (i.e., several runs), instantaneous data acquisition, and the optimization of data collection due to automatic synchronization among all the built-in sensors. However, to the best of our knowledge, no research has been conducted yet to evaluate MV through IMUs in the domain of alpine skiing, nor has it been evaluated regarding how the characteristics of the terrain (flatter vs. steeper slopes) and course setting (gate offset: i.e., turned vs. straighter courses) influence skier MV.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there have been further developments in the area of motion quality assessment in alpine skiing. Yamagiwa and colleagues developed a simple system based on a single IMU mounted on the trunk of a skier to assess skiing quality based on turning tempo (turn frequency) [ 16 ]. The algorithm assessed only the variability of tempo during a run in order to differentiate between high- and low-skill skiers.…”
Section: Introductionmentioning
confidence: 99%